Sharing of cultural values and heritage through storytelling in the digital age - Zort, Çağın; Karabacak, Esra; Öznur, Şevket; Dağlı, Gökmen (Frontiers in Psychology, 2023)
Sharing cultural values for generations is highly important. Especially establishing online learner communities for heritage through storytelling puts an emphasis on the sustainability of the welfare of the societies. In this respect, the aims of this study are to evaluate experts’ opinions on sharing cultural values on the digital platform based on their experience, the roles of educators and families with respect to the sharing of cultural values through storytelling in digital platforms, and also capture how cultural values be can be explained with metaphors in digital platforms. A focus group interview was conducted with teachers and vice headmasters from public primary and secondary schools in the Northern part of Cyprus within the age range of 30-50 years that are considered to be experts based on their 10 years and above of teaching experience. Data were analyzed through line-by-line coding to create themes. Findings revealed that cultural values are eroding, and in sharing cultural values with storytelling in the online environment, the role of educators and families is essential. Cultural values are the treasures and mirrors of society that should be preserved and transmitted to the younger generations and this can be accomplished through participation in digital platforms, and when such participatory cultural heritage projects are planned with a community-oriented background and human-centered computing concentration. This research sheds a light to indicate the importance of storytelling approach for sharing cultural values and heritage. It is significant to address the merits of technology in transferring cultural values and heritage. In addition to this, study is limited to the one specific context that can be further explored as cross cultural analysis.